Functional Genomics Uncovers Pleiotropic Role of Rhomboids in Corynebacterium glutamicum - Luenenschloss, Andrea; ter Veld, Frank; Albaum, Stefan P.; Neddermann, Tobias M.; Wendisch, Volker F.; Poetsch, Ansgar (Frontiers in Microbiology, 2022)
The physiological role of ubiquitous rhomboid proteases, membrane-integral proteins that cleave their substrates inside the lipid bilayer, is still ill-defined in many prokaryotes. The two rhomboid genes cg0049 and cg2767 of Corynebacterium glutamicum were mutated and it was the aim of this study to investigate consequences in respect to growth phenotype, stress resistance, transcriptome, proteome, and lipidome composition. Albeit increased amount of Cg2767 upon heat stress, its absence did not change the growth behavior of C. glutamicum during exponential and stationary phase. Quantitative shotgun mass spectrometry was used to compare the rhomboid mutant with wild type strain and revealed that proteins covering diverse cellular functions were differentially abundant with more proteins affected in the stationary than in the exponential growth phase. An observation common to both growth phases was a decrease in ribosomal subunits and RNA polymerase, differences in iron uptake proteins, and abundance changes in lipid and mycolic acid biosynthesis enzymes that suggested a functional link of rhomboids to cell envelope lipid biosynthesis. The latter was substantiated by shotgun lipidomics in the stationary growth phase, where in a strain-dependent manner phosphatidylglycerol, phosphatidic acid, diacylglycerol and phosphatidylinositol increased irrespective of cultivation temperature.